Direct experience and attitude change towards bears and wolves. Issue 3 (1st May 2015) - Eriksson, Max; Sandström, Camilla; Ericsson, Göran
Abstract : Understanding how changes in the sizes of large carnivore populations affect the attitudes of the public is vital in order to mitigate social conflicts over large carnivore management issues. Using data from two Swedish postal surveys in 2004 and 2009, we examined the probable social effects of a continued increase in the Swedish populations of bear and wolf by comparing levels of direct experience of bears and wolves with public attitudes towards these animals. We report an increase in direct experience of bears and wolves, lower levels of acceptance of the existence of these animals, and a lower degree of support for the policy goals of both species in 2009 compared to 2004. We also find that these changes are more prominent in areas with local carnivore populations than in other areas of Sweden. Our results imply that attitudes towards bears and wolves are likely to become more negative as populations continue to grow. The uneven distributions of the carnivore populations are likely to generate more frequent social conflicts in the future as they could cause an increase in the attitudinal divide between those members of the Swedish public who have had direct experiences of carnivores and those who have not.